Advanced Speed Control of a Three Phase Induction Machine Based on Rotor and Stator Flux Orientation Utilizing ANNs Technique - Ahmed Ateya Allu (PROSPECTIVE RESEARCHES, 2023)
This paper presents a design approach to enhance speed estimation and control for three phase induction machine drive system by the implementation speed sensor less field orientation technology. A Direct Stator Flux Oriented method integrated by Artificial Neural Network is followed to evaluate the machine speed and Indirect Rotor Flux Oriented method with Hysteresis Band Pulse Width Modulation is employed to for the system control. This control model allows sinusoidal currents to drive the motor with producing less speed and torque ripples, which minimizes the acoustic noise provides by fieldweakening operation at high and low-speeds. Computer simulation that is using Mat labsoftware shows acceptable controlled performance results for forward and reverses for motoring and generating operation. At the machine is motoring, speed range of (0- ±1250 rpm) with mechanical load torque variation up to (7 N-m) during steady state and dynamic condition.